# Resolve each of t

Here, coefficient of (2a – b)2 = 1, coefficient of (2a – b) = 2 and constant term = - 8

We shall now split up the coefficient of middle term i.e., 2 into two parts whose sum is 2 and product is -8 (1) = - 8

Clearly,

4 - 2 = 2 and,

4 (-2) = - 8

So, we replace 2 (2a – b) = 4 (2a –b) – 2 (2a – b)

Thus, we have

(2a – b)2 + 2 (2a – b) – 8 = (2a – b)2 + 4 (2a – b) – 2 (2a – b) - 8

= (2a – b) (2a – b + 4) – 2 (2a – b + 4)

= (2a – b – 2) (2a – b + 4)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics